2007
DOI: 10.1111/j.1745-7254.2007.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of valproate in Chinese children with epilepsy

Abstract: Aim: The aim of the present study is to establish a population pharmacokinetic (PPK) model of valproate (VPA) in Chinese epileptic children to promote the reasonable use of anti-epileptic drugs. Methods: Sparse data of VPA serum concentrations from 417 epileptic children were collected. These patients were divided into 2 groups: the PPK model group (n=317) and the PPK valid group (n=100). The PPK parameter values of VPA were calculated by NONMEM software using the data of the PPK model group. A basic model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 27 publications
1
41
0
2
Order By: Relevance
“…Table summarizes the characteristics of each study. Most of the models were developed in patients with epilepsy . One study reported a model incorporating data from both epileptic and psychiatric patients .…”
Section: Resultsmentioning
confidence: 99%
“…Table summarizes the characteristics of each study. Most of the models were developed in patients with epilepsy . One study reported a model incorporating data from both epileptic and psychiatric patients .…”
Section: Resultsmentioning
confidence: 99%
“…To assess the accuracy and precision of the concentration prediction, the mean prediction error (MPE), mean squared prediction error (MSPE), root mean-squared prediction error (RMSPE), weight residues (WRES), and the 95% confidence intervals (95% CI) were calculated. Then, the values of the two models were compared [19] . The shrinkage for each of the parameters in the model was evaluated using the method described by Karlsson [20] .…”
Section: Model Validationmentioning
confidence: 99%
“…Therefore the variation of the apparent mobility will provide information to facilitate the study of the conduction mechanism. However, up to now all the measurements of apparent mobilities by the above electrochemical technique are carried out with two-band electrodes, [6][7][8]13 which is difficult to eliminate the influence of contact resistance. In our insight, four-probe method has not been applied in this new electrochemical technique to measure in-situ apparent mobility.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an electrochemical technique on the basis of two-probe method was successfully developed to measure the in-situ mobility under different doping potentials. [6][7][8]13 Thus measured mobilities are apparent mobilities since the evaluation is based on a single-carrier model. The apparent mobility of charge carriers in a polymer film will vary if the sort of charge carriers changes as the oxidation state of the polymer proceeds.…”
Section: Introductionmentioning
confidence: 99%